A cross sectional study to compare serum beta 2 microglobulin levels in oral leukoplakia and oral squamous cell carcinoma patients - Kulkarni, S. R.; Garud, Yogesh Prakash (International Surgery Journal, 2019)
Background: One of the major health problems in the world is cancer. More than 11 million people are diagnosed yearly with cancer. Oral cancer is one of the deadliest cancers. Oral cancer is generally preceded by precancerous lesions. India has highest number of oral cancer patients. β2 microglobulin (β2 m) is one of the tumor markers. Methods: We are correlating serum levels of beta 2 microglobulin in leukoplakia and oral squamous cell carcinoma. In our study, the serum β2 m levels were estimated in 2 groups of 30 subjects each with oral squamous cell carcinoma (OSCC) designated as Group A, 30 subjects with oral leukoplakia designated as Group B. Results: There were majority of participants from age group of 51 to 70 years (Group A-60%, Group B-53.33%). Group A had majority of females 20 (66.67%) while males were 10 (33.33%). Group B had majority of males 18 (60.00%) while females were 12 (40.00%). Major adverse habit was tobacco chewing (83.33% Group A and 73.33% in group B). Most common site was Left BM. Right BM was second. There was significant association between the groups and serum β2 m levels. Mean levels of Group A patients were 3.13±0.47 mg/L and Group B 1.43±0.29 mg/L. Conclusions: Adverse habits like tobacco chewing, smoking and alcohol increase chances of oral cancers and precancerous lesions. Significant correlation between oral cell carcinoma cases and serum β2 m levels is seen.